CONVERSATION ANALYSIS: THESIS SUPERVISION AT JAMBI UNIVERSITY: Thesis Supervision at Jambi University - Aura Fara Aulia (Universitas Jambi, 2018)
This study presents an analysis of student-supervisor consultation as the example of institutional talk. The purposes of this study are to analyze how supervisor assessed student’s capability to conduct her topic, how student designed her talk to get the needed information from the supervisor and how both of them managed to deal with potential problem in their talk. The present study uses Conversation Analysis (CA) method, where the data of thesis supervision discussion was recorded and transcribed, the unique phenomena and their patterns were identified, and they were interpreted to see the relation to the broader matrix of interaction. The data of this study is a recording of thesis supervision between Jambi University’s student and her supervisor. From the analysis, it is found that both the student and the supervisor actively participated in the discussion according to their own roles in the institutional talk. The supervisor assessed the student’s capability in conducting her proposed thesis in many interactive ways that involved asking questions and giving feedbacks. The student’s talk was well constructed where her questions and the way she delivered it also show her own good capability in comprehending the issues under discussion. Last, both student and supervisor were found to be well-aware of the problems arose in their conversation and were able to cover it together in their own role in the institutional talk. This suggested mutual effort in bringing the supervision meeting forward to reach their intended goal. Keywords: Conversation Analysis, Institutional Talk, Thesis Supervision, Jambi University